2013
DOI: 10.1016/j.techfore.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Spatial connectivity as a recovery process indicator: The L'Aquila earthquake

Abstract: The main objective of this paper is to prove that spatial connectivity can be an effective spatial indicator for monitoring and evaluating the recovery process after the event of an earthquake. It integrates variables such as distance, travel time and quality of public transport service. We hypothesize that there is a relationship between the connectivity to the central business districts in cities, and the satisfaction with the locations of new settlements assigned to the homeless population during a recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…There is a strong correlation between the dissatisfaction among people who relocated to new settlements and the distance and travel time to central L'Aquila (Contreras et al 2013). There were emergent groups that wanted to regain social space for L'Aquila through the location in the new settlements of amenities such as multifunctional centers (including auditorium, library, multimedia, and playground spaces for children).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a strong correlation between the dissatisfaction among people who relocated to new settlements and the distance and travel time to central L'Aquila (Contreras et al 2013). There were emergent groups that wanted to regain social space for L'Aquila through the location in the new settlements of amenities such as multifunctional centers (including auditorium, library, multimedia, and playground spaces for children).…”
Section: Discussionmentioning
confidence: 99%
“…The main objective is to reduce the emigration of young people from the city of L'Aquila (Forino 2014). Most of the new settlements lack any urban facilities, a characteristic of the relief phase when most of the facilities are not available due to damage, but in this case due to the lack of urban planning in the design of the new settlements (Contreras et al 2013). These problems contrast with the advanced seismic design of the houses, more related to the development phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in reality most settlements have been located in the periphery of the city, and in this way they contributed to strengthening the already dispersed urban tissue of L'Aquila (See Figure 1). Research has shown that the residents of the new settlements show more propensity to move to another place of residence (Contreras et al, 2013). However, relocation would not necessarily imply returning to the previous place of residence, as the reconstruction in large parts of the city has not yet been completed.…”
Section: L'aquila: a Smart Citymentioning
confidence: 99%